Examining the Borobudur temple’s affective image, cognitive image, and visitor satisfaction in predicting revisit intention - Masykuri, Ardhana Reswari; Nurbaeti; Mumin, Adhi Trirachmadi (International Journal of Applied Sciences in Tourism and Events, 2023)
This study examines how affective and cognitive image influence revisitation intentions to Borobudur Temple, with visitor satisfaction as an intervening variable. While previous tourism re- search has predominantly emphasized visitor satisfaction as the primary predictor of revisit intentions, there is limited research on the impact of affective and cognitive image on return intentions, particu- larly at cultural heritage sites in the new normal following the Covid-19 pandemic. Affective image sig- nificantly influences word-of-mouth recommendations and the intention to return, which holds critical implications for the sustainability of tourism destinations. Quantitative data were gathered from 204 non-probability sampled respondents, of which 82.8% were domestic tourists and 17.2% were overseas tourists. Contrary to earlier theories about destination cog- nitive image, this study challenges several hypotheses. It reveals that cognitive image does not signif- icantly influence visitor satisfaction or the intention to revisit. However, visitor satisfaction effectively mediates the relationship between affective image and revisitation intentions, but not with cognitive image. The study concludes with recommendations for decision-makers and suggestions for future research.